Social media as a new space for communication and Muslim identity formation - Ririn Anugerah Ikasatya; Cahya Apriliani (The Journal of Religion and Communication Studies, 2026)
Background: This study discusses the role of social media, particularly Instagram and TikTok, as a space for the formation of Islamic identity among Indonesian Muslim youth amid a highly visual and competitive digital culture. The transformation of religious communication in the digital space marks the emergence of the phenomenon of digital religiosity, where piety is displayed through symbols, visual narratives, and online participation. Methods: A quantitative descriptive approach supported by qualitative analysis was used on 50 Muslim youth respondents who are active social media users. Data were collected through an online survey using a five-point Likert scale and analyzed using descriptive statistics and content analysis of open-ended responses. Findings: The results show that social media plays a significant role in shaping Muslim identity, especially among women aged 20–22 years. Islamic content on social media was found to increase understanding of Islamic values, motivation to worship, and reflective expressions of religiosity. However, the study also found ethical challenges such as digital riya' and algorithmic religiosity, where religious practices can shift to become performative due to the logic of popularity and platform algorithms. Conclusion: Social media functions as a laboratory for religious identity for Muslim youth, mediating between spiritual expression and popular culture while demanding strong religious digital literacy. Novelty/Originality of this article: This study offers a new perspective through the integration of social identity and digital communication theories in the study of Islamic communication, as well as introducing the concept of digital Islamic identity as a form of reflective piety in the online space.